Jawabanmu

2014-08-25T16:15:30+07:00
A. 7x+3y+4z + x+y+z = 8x+4y+5z
b. -3x+3y -(-3x+2y) = -3x+3y+3x-2y = y
c 3x+3y-z -(-3x+3y+z) = 3x+3y-z+3x-3y-z = 6x-2z
Jawaban yg c tolong dikoreksi lagi
eh iya typo, thanks gan
iya sipp
Jawaban paling cerdas!
2014-08-25T16:21:23+07:00
Jumlahkan 7x + 3y + 4z dan x + y + z
= (7x + 3y + 4z) + (x + y + z)
= 8x + 4y + 5z

kurangkan -3x+2y dari -3x +3y
= (-3x + 3y) - (-3x + 2y)
= -3x + 3y + 3x - 2y
= y

kurangkan -3x+3y+z dari 3x+3y-z
= (3x + 3y - z) - (-3x + 3y + z)
= 3x + 3y - z + 3x - 3y - z
= 6x - 2z
2 5 2